Effect of aditive supplementation to ensiled red clover on voluntary intake, digestibility and N balance - Marina Vranić; Mladen Knežević; Krešimir Bošnjak; Goran Perčulija; Josip Leto; Hrvoje Kutnjak; Ivana Matić (Mljekarstvo)
The objective of this study was to determine effect of additive supplementation to red clover silage on ad libitum intake of fresh silage and dry matter (DM), in vivo digestibility of DM, organic matter (OM), OM in DM (D-value), crude protein (CP) and nitrogen (N) balance. Red clover was harvested at 60% bloom stage. It was ensiled into round bales without an additive (CD) and with an additive supplementation (CDA) in the amount of 2 L t-1 fresh material. Statistically lower (P<0.001) DM content was recorded in CD (405 g kg-1 fresh sample) in comparison with CDA (665 g ST kg-1 fresh sample). Statistically higher CP content (P<0.001) was recorded in CD (127 g kg-1 ST) in comparison with CDA (110 g SP kg-1 ST). CD had lower pH (P<0.001) (4.9) in comparison with CDA (5.2). No differences were recorded in NH3 between treatments. Ad libitum intake of fresh silage and silage DM was higher (P<0.001 and P<0.01, respectively) in CD in comparison with CDA. Digestibility of DM, OM, CP, D-value and N balance were not different between treatments. It was concluded that the positive effect of additive supplementation to red clover silage on chemical composition, ad libitum intake, digestibility and N balance was not recorded due to applied ensiling technology as additive can improve feeding value of roughage, but it is not a replacement for good management practices.